Strategi Kesantunan Dalam Melayangkan Protes di Restoran Jepang Kajian Sosiopragmatik - Maharani Patria Ratna (Diponegoro University, 2020)
A protest is something that really needs to be careful in its delivery. This study examines the strategy of buyers in protesting at a Japanese restaurant. This research is a qualitative descriptive study with the data collection method of the literature method. The technique used is documentation techniques, namely data collection techniques through reading text or text reading, assessment, and recording all literature related to this research. The results achieved in this study will be presented in the form of a description. The results of this study indicate that the dominant strategy used by buyers to cast protests is to adopt a bald on record strategy. This strategy was chosen because protest is a form of dissatisfaction made because buyers feel they do not receive Omotenashi from the restaurant. In order to express dissatisfaction, the buyer is forced to threaten the shop assistant's face as an interlocutor. However, it should be noted that in certain contexts, Enryo is still a consideration for buyers in protesting, even though the potential is very small or not dominant.